Density Dependence in Large Herbivores Inhabiting an Insular Nature Reserve - Cornelius J. Louw; Francesca Parrini; Jason P. Marshal (Ecology and Evolution)
ABSTRACT While studies often focus on density‐dependent responses of ungulate populations to resource limitations at large spatial scales, the dynamics at smaller scales remain relatively unexplored. To address this gap, we investigated the temporal dynamics of ungulate abundance in a small dystrophic grassland ecosystem over 20 years, with minimal management interventions. We used annual counts and herd composition data to explore density‐dependent responses at the population level and attempt to link such responses to demographic mechanisms. Counts were corrected using a state‐space modeling approach. Populations of most species increased from low densities to approximate equilibrium densities. Our findings reveal evidence of density‐dependent responses in population growth that shaped the population abundance dynamics. Additionally, juvenile‐to‐adult ratios exhibited patterns of density‐dependent reductions in recruitment. This study suggests grassland ecosystems with moderate annual rainfall are regulated primarily by bottom‐up processes.